1985
DOI: 10.1007/bf02388772
|View full text |Cite
|
Sign up to set email alerts
|

Cerebro-costo-mandibular syndrome with consanguinity

Abstract: The cerebro-costo-mandibular syndrome is a rare disorder characterized by unique posterior rib defects, micrognathia, and mental deficiency. The mode of transmission is undetermined. This report describes the first case with documented parental consanguinity as well as hitherto undescribed CT and skeletal findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1987
1987
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Associated skeletal anomalies reported in patients with CCM have included hypoplastic humerus [4], sacral fusion and a flask-shaped configuration of the pelvis [5], hemivertebrae, clubfoot, hip dislocation, and elbow dysplasia [6], pectus carinatum [7], hypoplasia of the sternum, clavicles, and pubic rami [2]. Our patient is the first to demonstrate epiphyseal stippling.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Associated skeletal anomalies reported in patients with CCM have included hypoplastic humerus [4], sacral fusion and a flask-shaped configuration of the pelvis [5], hemivertebrae, clubfoot, hip dislocation, and elbow dysplasia [6], pectus carinatum [7], hypoplasia of the sternum, clavicles, and pubic rami [2]. Our patient is the first to demonstrate epiphyseal stippling.…”
Section: Discussionmentioning
confidence: 75%
“…Of the nearly 50% of patients with CCM who survived, half had varying degrees of mental deficiency. Clarke and Nguyen described an infant, the product of a father/daughter union, who had microcephaly, a large porencephalic cyst and no definable ventricular system or interhemispheric fissure [2]. Merlob et al reported a patient with CCM whose in-utero ultrasound showed "a fluid-filled supratentorial" compartment [3].…”
Section: Discussionmentioning
confidence: 98%
“…Microcephaly of postnatal onset may be present (40%), sometimes associated with structural cerebral anomalies [Plotz et al, 1996]. So far these have been detected in only three living patients by ultrasound and CT scan, and they include large porencephalic cyst and no definable ventricular system or interhemispheric fissure in one case; agenesis of the corpus callosum with ''enhancement'' of the right leaf of the tentorium and enlargement of both lateral ventricles in another, and ''fluid filled supratentorial'' compartment in yet another [Clarke and Nguyen, 1985;Merlob et al, 1987;Burton and Oestreich 1988]. Exceptionally, intrauterine growth retardation and rib anomalies could be seen by ultrasound examination during pregnancy, but usually prenatal diagnosis is very difficult and probably restricted to families with a positive history for CCMS [Merlob et al, 1987].…”
Section: Discussionmentioning
confidence: 97%
“…However, so far during life in only three living patients structural cerebral anomalies have been detected by ultrasound and CT scan [Burton et al, 1988;Clarke and Nguyen, 1985;Merlob et al, 19871. Microcephaly, a large porencephalic cyst, and no definable ventricular system or interhemispheric fissure was described by Clarke and Nguyen [1985] in their patient. Merlob et al [19871 reported a patient whose prenatal ultrasound study showed "a fluid-filled supratentorial" compartment.…”
Section: Ccm Syndrome 291mentioning
confidence: 98%
“…Forty-eight cases [Burton and Oestreich, 1988;Caffey, 1973;Clarke and Nguyen, 1985;DrossouAgakidou et al, 1991;Faur6 et al, 1978;Feldman and Heyman, 1987;Fidalgo Alvarez et al, 1988;Gurgey et al, 1985;Harris and Fellows, 1977;Hennekam et al, 1985;Kang et al, 1992;Kemperdick and Lemburg, 1976;Kringelbach and Henriksen, 1968;Kuhn et al, 1975;Langer Jr. and Herrmann, 1974;Leroy JG et al, 1981;Lim and Koh, 19921;McNicholl et al, 1970;Meineke et al, 1987;Merlob et al, 1987;Miller et al, 1972;Mohan and Mandalam, 1982;Nicholls and Fletcher, 1973;Schroer and Meyer, 1985;Silverman et al, 1980;Simma et al, 1989;Smith et al, 1966;Smith and Sekar, 1985;Tachibana et al, 1980;Trautman et al, 1985;Walizadeh, 1978;Williams and Sane, 19761 have been reported to date. Severe micrognathia and posterior rib-gap defects on chest roentgenographs are constant findings.…”
Section: Introductionmentioning
confidence: 99%